Human umbilical cord mesenchymal stem cell-derived exosomes mitigate acute radiation-induced intestinal oxidative damage via the Nrf2/HO-1/NQO1 signaling pathway - Hongyu Wang; Jinbao Wang; Gaosheng Yang; Yanjie Li; Weikai Chen; Jianping Yu; Xiaopeng Han (PLoS ONE, 2025)
Acute radiation-induced intestinal injury (ARII), a prevalent complication of abdominal radiotherapy, remains clinically challenging due to limited therapeutic options. This study demonstrates the therapeutic efficacy of human umbilical cord mesenchymal stem cell-derived exosomes (hucMSC-Exos) in mitigating ARII through Nrf2/HO-1/NQO1 pathway activation. In a rat model receiving 12 Gy abdominal irradiation, systemic hucMSC-Exos administration significantly restored intestinal mucosal integrity and reduced oxidative damage markers. Mechanistically, hucMSC-Exos potentiated the antioxidant axis by upregulating Nrf2 signaling, as evidenced by histopathological, biochemical, and molecular analyses. Complementary in vitro experiments revealed hucMSC-Exos protected irradiated IEC-6 cells from oxidative dysfunction while enhancing proliferation, effects substantially attenuated upon Nrf2 silencing via siRNA. These findings establish that hucMSC-Exos orchestrate redox equilibrium through targeted Nrf2 pathway modulation, effectively counteracting radiation-induced enterocyte apoptosis. The elucidated mechanism expands the therapeutic paradigm of MSC-derived exosomes in radioprotection and provides a clinically translatable strategy for managing ARII in oncological radiotherapy.